HASIL BELAJAR PESERTA DIDIK TENTANG MACAM-MACAM GAYA DENGAN MENGGUNAKAN WHITEBOARD ANIMATION DI KELAS IV SD NEGERI 22 LAHAT - Rinta Viranda Karim; Toybah Toybah; Mashannuddin Mashannuddin (Jurnal Inovasi Sekolah Dasar, 2021)
AbstractThis study aims to describe efforts to improve learning outcomes of the fourth grade students in type of forces materials using Whiteboard Animation Media at Elementary School number 22 Lahat. This research applied classroom action research method with three cycles of action. The research subjects were fourth grade students, with the total of 9 students consisting of 4 boys and 5 girls. The results of the study indicated that the value of student learning outcomes has increased. This can be seen in the percentage of student learning completeness in the first cycle of 55.5%, the second cycle increased to 77.7%, the third cycle increased to 88.8%. In addition, based on the results of observations, scores of students’ activities have increased. In the first cycle, the percentage of student activity in learning reaches 61.5% with a moderately active category. In the second cycle, it has increased to 70.3% with an active category. In the third cycle, it increased to 80.5% in the very active category. This indicated that the application of Whiteboard Animation Learning Media can improve the learning outcomes of fourth grade students about type of forces materials at SD Negeri 22 Lahat.             Keywords: Whiteboard Animation media, learning outcomes. AbstrakPenelitian ini bertujuan untuk mendeskripsikan upaya peningkatan hasil belajar peserta didik kelas IV tentang macam-macam gaya menggunakan Media Whiteboard Animation di SD Negeri  22 Lahat. Penelitian ini menggunakan metode penelitian tindakan kelas dengan tiga siklus tindakan. Subjek penelitian adalah peserta didik kelas IV, yang berjumlah 9 peserta didik terdiri dari 4 laki-laki dan 5 perempuan. Dari hasil penelitian menunjukkan bahwa nilai hasil belajar peserta didik mengalami peningkatan, hal ini terlihat pada persentase ketuntasan belajar peserta didik di siklus I sebesar 55,5%, siklus II mencapai 77,7 %, siklus III persentase ketuntasan belajar peserta didik meningkat mencapai 88,8%. Selain itu, aktivitas peserta didik yang mengalami peningkatan, pada siklus I presentase aktivitas peserta didik dalam belajar mencapai 61,5% dengan kategori cukup aktif, pada siklus II mengalami peningkatan menjadi 70,3% dengan kategori aktif, dan pada siklus III mengalami peningkatan menjadi 80,5% dengan kategori sangat aktif. Hal ini membuktikkan bahwa melalui Media Pembelajaran Whiteboard Animation dapat meningkatkan hasil belajar peserta didik kelas IV tentang macam-macam gaya di SD Negeri  22 Lahat. Kata kunci : Media Whiteboard Animation, hasil belajar.